2012
DOI: 10.1021/nl3035256
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Conductance in an InSb Nanowire

Abstract: Ballistic one-dimensional transport in semiconductor nanowires plays a central role in creating topological and helical states. The hallmark of such one-dimensional transport is conductance quantization. Here we show conductance quantization in InSb nanowires at nonzero magnetic fields. Conductance plateaus are studied as a function of source-drain bias and magnetic field, enabling extraction of the Landég factor and the subband spacing. KEYWORDS:Conductance quantization, ballistic transport, quantum point co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
198
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(208 citation statements)
references
References 45 publications
8
198
2
Order By: Relevance
“…Past studies have shown that nanowires can grow along nanosteps and nanogrooves on nanofaceted sapphire substrate. 23,24,[40][41][42] This mode of guided growth, which we refer to as graphoepitaxy, has proven to be dominant over epitaxial growth, and essentially overrules the epitaxial relations between the sapphire and the nanowire. 28,29,40,41,44 This was the case also for the core-shell guided nanowires, as can be seen in figure 3.…”
Section: Graphoepitaxial Guided Growth On Faceted Sapphire Substratesmentioning
confidence: 99%
“…Past studies have shown that nanowires can grow along nanosteps and nanogrooves on nanofaceted sapphire substrate. 23,24,[40][41][42] This mode of guided growth, which we refer to as graphoepitaxy, has proven to be dominant over epitaxial growth, and essentially overrules the epitaxial relations between the sapphire and the nanowire. 28,29,40,41,44 This was the case also for the core-shell guided nanowires, as can be seen in figure 3.…”
Section: Graphoepitaxial Guided Growth On Faceted Sapphire Substratesmentioning
confidence: 99%
“…[4][5][6][7] However, preliminary experiments probing Majorana bound states in nanowires were marked by disorder and a soft superconducting gap in the tunneling regime. [4][5][6][7][8] Disorder in nanowire systems is known to break up ballistic transport 9,10 , which is a crucial ingredient for developing 1D topological superconductivity. 1,2,4,9 Additionally, disorder can produce zero-bias conductance signatures similar to Majorana bound states.…”
Section: Mainmentioning
confidence: 99%
“…[4][5][6][7][8] Disorder in nanowire systems is known to break up ballistic transport 9,10 , which is a crucial ingredient for developing 1D topological superconductivity. 1,2,4,9 Additionally, disorder can produce zero-bias conductance signatures similar to Majorana bound states. 11 While the typical signature of ballistic 1D transport-quantized conductance-has been observed in InSb nanowires at high magnetic field 9 and more recently at zero-field, 19 clear demonstrations of ballistic transport at lower fields (< 1T, i.e., before the expected onset of topological superconductivity) in hybrid nanowire-superconductor systems are lacking.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…The velocity of the excitations is strongly renormalized by SOI, which opens a way to fine-tune the charge and spin response of 1D electrons by changing the gate potential. One of the modes softens upon increasing the gate potential to enhance the current response as well as the power dissipated in the system.Introduction.-Today we are witnessing the burst of interest in the ballistic electron transport in quantum wires [1][2][3][4][5]. For the last three decades the quantum wires formed by electrostatic gating of a high-mobility two-dimensional (2D) electron gas have been the favorite playground to study quantum many-body effects in one-dimensional (1D) electron systems [6], where a strongly correlated state known as the Tomonaga-Luttinger liquid emerges as a result of the electron-electron (e-e) interaction [7].…”
mentioning
confidence: 99%